2021
DOI: 10.1007/s11440-020-01133-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal soil-structure interface model based on critical state theory

Abstract: In energy geostructures, the soil-structure interface is subjected to thermo-mechanical loads.In this study, a non-isothermal soil-structure interface model based on critical state theory is developed from a granular soil-structure interface constitutive model under isothermal conditions. The model is capable of capturing the effect of temperature on sand/clay-structure interfaces under constant normal load and constant normal stiffness conditions. First, the developed model was verified for sand-structure int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…( 40) into (23), which gives: According to Eq. ( 40), the thermal volume change depends on the accuracy of coefficient k. However, many experimental results revealed that the coefficient k depends on the property of soils including OCR, initial void ratio, plasticity index [1,6,7,9,10,13,14,16,18,26,30,38,39,44,46,48,63,64,76,79,80,91]. Thermal volume change, on the other hand, is almost independent of suction, according to Uchaipichat and Khalili [80].…”
Section: Temperature-dependent Function Of Void Ratiomentioning
confidence: 99%
“…( 40) into (23), which gives: According to Eq. ( 40), the thermal volume change depends on the accuracy of coefficient k. However, many experimental results revealed that the coefficient k depends on the property of soils including OCR, initial void ratio, plasticity index [1,6,7,9,10,13,14,16,18,26,30,38,39,44,46,48,63,64,76,79,80,91]. Thermal volume change, on the other hand, is almost independent of suction, according to Uchaipichat and Khalili [80].…”
Section: Temperature-dependent Function Of Void Ratiomentioning
confidence: 99%
“…Human activities, such as disposal of high-level radioactive nuclear wastes, geothermal heat storage, energy geostructures (piles, walls and slabs) and buried high voltage cables, disturb the temperature equilibrium of ground (Brandon et al 1989;Ghorbani et al 2020;Lahoori 2020;Lahoori et al 2021;Maghsoodi et al 2021;Motamedi et al 2021;Murphy et al 2015;Tourchi et al 2021;Bai et al 2021;Tang et al 2021). The temperature disturbance may impact the soil physico-mechanical parameters such as shear strength, volumetric behaviour and pore water pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Human activities, such as disposal of high-level radioactive nuclear wastes, geothermal heat storage, energy geostructures (piles, walls and slabs) and buried high voltage cables, disturb the temperature equilibrium of ground (Brandon et al 1989;Ghorbani et al 2020;Lahoori 2020;Lahoori et al 2021;Maghsoodi 2020;Maghsoodi et al 2021;Menaceur et al 2021;Motamedi et al 2021;Murphy et al 2015;Tourchi et al 2021). The temperature disturbance may impact the soil physico-mechanical parameters such as shear strength, volumetric behaviour and pore water pressure.…”
Section: Introductionmentioning
confidence: 99%